Spanish Foreign Direct Investments in Latin America:: Internationalization Strategies and Financial Management Practices - Curci, Roberto; Cardoza, Guillermo (Journal of Comparative International Management, 2009)
This study analyzes the internationalization strategies and the financial management practices of seven Spanish companies with the largest volume of investments in Latin America. The companies selected for an in-depth analysis represent approximately 80 percent of the total Spanish foreign investments during the period of analysis. Their investments have taken place mainly in service sectors such as banking, energy, and telecommunications. The study identifies the market conditions and the corporate strategies that have allowed these Spanish companies to successfully initiate and expand business activities into Latin America. The findings suggest Spanish investors have strengthened their global competitiveness and have accomplished greater financial results.